PERAN WANITA DALAM PERSPEKTIF SOSIO-DEMOGRAFIS PADA MASYARAKAT ADAT KUTA DI KECAMATAN TAMBAKSARI, KABUPATEN CIAMIS, JAWA BARAT - Dadi D (LITERASI: Indonesian Journal of Humanities, 2012)
Adat communities are known for their local wisdoms. Kuta Kampong of the Tambaksari district, Ciamis regency is known for having local wisdoms enabling to sustain their cultural unity and environment. It is shown that Kuta women has a multiple role in the households. A part from giving a birth and caring children, the women also partake actively in economic sector as red sugar makers and also in employments normaly filled by men/ husbands. The women of Kuta are also equal to men in providing a solution for household problems, including in making decision about how many children to have, though final decisions are made by their husbands. From an adat perspective, the Kuta households also hold the view that the number of children should be adjusted to the carrying capacity of their environment. Based on these considerations, the Kuta households prefer having small number of children. Keywords: Kuta kampong, adat community, local wisdoms, women role, sociodemography